Optimal interest rate rules and inflation stabilization versus price-level stabilization - Marc P. Giannoni (Federal Reserve Bank of New York, 2012)
This paper compares the properties of interest rate rules such as simple Taylor rules and rules that respond to price-level fluctuations - called Wicksellian rules - in a basic forward-looking model. By introducing appropriate history dependence in policy, Wicksellian rules perform better than optimal Taylor rules in terms of welfare and robustness to alternative shock processes, and they are less prone to equilibrium indeterminacy. A simple Wicksellian rule augmented with a high degree of interest rate inertia resembles a robustly optimal rule - that is, a monetary policy rule that implements the optimal plan and is also completely robust to the specification of exogenous shock processes.
Keywords: E30; E31; E52; E58; 330; optimal monetary policy; Taylor rule; robust policy